2020
DOI: 10.1186/s40462-020-0195-z
|View full text |Cite
|
Sign up to set email alerts
|

Understanding decision making in a food-caching predator using hidden Markov models

Abstract: Background: Tackling behavioural questions often requires identifying points in space and time where animals make decisions and linking these to environmental variables. State-space modeling is useful for analysing movement trajectories, particularly with hidden Markov models (HMM). Yet importantly, the ontogeny of underlying (unobservable) behavioural states revealed by the HMMs has rarely been verified in the field. Methods: Using hidden Markov models of individual movement from animal location, biotelemetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…The African leopard ( Panthera pardus ) is a generalist predator (Hayward et al., 2006; Shehzad et al., 2015), actively hunting for its prey but also taking carrion whenever present (Bothma & Walker, 2013; Stuart & Stuart, 1993). Leopards usually cache their kills in bushes and consume them on the ground (Balme et al., 2007; Farhadinia et al., 2020; Karanth & Sunquist, 2000). However, competing guild predators such as spotted hyenas ( Crocuta crocuta ) and lions ( Panthera leo ) often discover and kleptoparasitize cached prey (Domínguez‐Rodrigo, 2001; Pitman et al., 2013; Volmer & Hertler, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The African leopard ( Panthera pardus ) is a generalist predator (Hayward et al., 2006; Shehzad et al., 2015), actively hunting for its prey but also taking carrion whenever present (Bothma & Walker, 2013; Stuart & Stuart, 1993). Leopards usually cache their kills in bushes and consume them on the ground (Balme et al., 2007; Farhadinia et al., 2020; Karanth & Sunquist, 2000). However, competing guild predators such as spotted hyenas ( Crocuta crocuta ) and lions ( Panthera leo ) often discover and kleptoparasitize cached prey (Domínguez‐Rodrigo, 2001; Pitman et al., 2013; Volmer & Hertler, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…hunting for its prey but also taking carrion whenever present (Bothma & Walker, 2013;Stuart & Stuart, 1993). Leopards usually cache their kills in bushes and consume them on the ground (Balme et al, 2007;Farhadinia et al, 2020;Karanth & Sunquist, 2000).…”
mentioning
confidence: 99%
“…Viterbi coded states also confirmed that homing behaviour typically ended at the den site. As noted Farhadinia et al (2020), this kind of verification of the behavioural states revealed by a hidden Markov model using field observations is relatively rare, but here we were able to do it. Therefore, our analysis provided new information on wolves foraging behaviour in summertime, which is relevant when, for example assessing the risk of human-wildlife conflict.…”
Section: Discussionmentioning
confidence: 72%
“…We assessed goodness of fit for the HMM using pseudo-residuals drawn from the fit model. Pseudo-residuals of the step length parameter should be normally distributed given good model fit (Farhadinia et al, 2020;Patterson et al, 2009). Therefore, we visually inspected step length pseudo residuals and used a Shapiro-Wilk normality test using a random subset of pseudo residual values (n = 1000).…”
Section: Hidden Markov Movement Modelsmentioning
confidence: 99%